Predicting difficult airway intubation in thyroid surgery using multiple machine learning and deep learning algorithms - Zhou, Cheng-Mao; Wang, Ying; Xue, Qiong; Yang, Jian-Jun; Zhu, Yu (Frontiers in Public Health, 2022)
Background: In this paper, we examine whether machine learning and deep learning can be used to predict difficult airway intubation in patients undergoing thyroid surgery. Methods: We used ten machine learning and deep learning algorithms to establish a corresponding model through a training group, and then verify the results in a test group. We used R for statistical analysis, and constructed the machine learning prediction model in Python. Results: The top 5 weighting factors for difficult airways identified by the average algorithm in machine learning were age, sex, weight, height and BMI. In the training group, the AUC values and accuracy and precision for Gradient Boosting were 0.932, 0.929, and 100%, respectively. As for the modeled effects of predicting difficult airways in test groups, among the models constructed by the ten algorithms, the three algorithms with the highest AUC values were Gradient Boosting, CNN and LGBM, with values of 0.848, 0.836, and 0.812, respectively; In addition, among the algorithms, Gradient Boosting had the highest accuracy with a value of 0.913; Additionally, among the algorithms, the Gradient Boosting algorithm had the highest precision with a value of 100%. Conclusion: According to our results, Gradient Boosting performed best overall, with an AUC greater than 0.8, an accuracy greater than 90%, and a precision of 100%. Besides, the top 5 weighting factors identified by the average algorithm in machine learning for difficult airways were age, sex, weight, height and BMI.